High performance embedded architectures and compilers [electronic resource] : second international conference, HiPEAC 2007, Ghent, Belgium, January 28-30, 2007 : proceedings - HiPEAC 2007 (2007 : Ghent, Belgium); Bosschere, Koen de; SpringerLink (Online service) (Berlin, Heidelberg : Springer-Verlag Berlin Heidelberg, 2007)
16